THE ROLE OF MOSQUES IN UTILIZING ZAKAT, INFAQ, AND SHADAQOH AS SUSTAINABLE SHARIA FINANCIAL INSTRUMENTS IN SURABAYA - Huda, Fatkur; Wijaya, M. Febriyanto Firman; Nadid, Erdin; Salsabilla, Salma Nadia; Al Farisi, Salman (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to explore the strategic role of mosques in managing Zakat, Infaq, and Shadaqah (ZIS) as sustainable Islamic financial instruments to support socio-economic empowerment in Surabaya. Design/Methodology/Approach: Using a qualitative descriptive approach, this research employed in-depth interviews and field observations across 14 selected mosques in five regions of Surabaya. Data were analyzed thematically to identify patterns in ZIS fund management and community empowerment practices. Research findings: The study finds that mosques in Surabaya actively collect and utilize ZIS funds for social aid and productive activities. Key strategies include enhancing human resource capacity, improving facilities and financial management infrastructure, raising public awareness, and building partnerships with Islamic financial institutions. Programs such as skill training, micro-enterprise support, and infrastructure development demonstrate the sustainable use of ZIS funds. Transparency and accountability are also emphasized to increase public trust. Theoretical Contribution/Originality: This study contributes to the literature by contextualizing mosque-based ZIS management in an urban Indonesian setting. It offers a structured strategy map tailored to the socio-economic characteristics of Surabaya and expands on existing empowerment models by integrating religious, financial, and institutional dimensions. Practitioners/Policy Implications: The findings provide actionable insights for mosque administrators, zakat institutions, and policymakers to enhance the sustainability of ZIS utilization. Recommendations include capacity-building for mosque amil, digitalization of ZIS systems, and policy support for mosque collaborations with Islamic financial institutions and government agencies. Research Limitations/Implications: The study is limited to 14 mosques, which may not fully represent the diversity of practices across Surabaya. The qualitative nature also limits generalizability. Future research should adopt a mixed-methods approach with broader samples and examine digital integration and long-term program outcomes for greater impact assessment.